2021
DOI: 10.3390/biomedicines9121879
|View full text |Cite
|
Sign up to set email alerts
|

ACTB Mutations Analysis and Genotype–Phenotype Correlation in Becker’s Nevus

Abstract: Becker’s nevus (BN) is a cutaneous hamartoma which is characterized by circumscribed hyperpigmentation with hypertrichosis. Recent studies have revealed that BN patients harbored postzygotic ACTB mutations, which were restricted to arrector pili muscle lineage. We screened for ACTB mutations in 20 Chinese patients with BN and found that recurrent mutations (c.C439A or c.C439T) in ACTB were detected in the majority of BN patients. However, more than 20% of the patients were negative for ACTB mutations, suggesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In 2021, Dai discovered ACTB mutations in dermal tissues other than the arrector pili muscle, suggesting that the arrector pili muscle is not the only source of ACTB mutations in BN. The study showed that patients with skin lesions covering more than 1% body surface area or located above the waist were more likely to carry ACTB mutations 22 …”
Section: Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Dai discovered ACTB mutations in dermal tissues other than the arrector pili muscle, suggesting that the arrector pili muscle is not the only source of ACTB mutations in BN. The study showed that patients with skin lesions covering more than 1% body surface area or located above the waist were more likely to carry ACTB mutations 22 …”
Section: Geneticsmentioning
confidence: 99%
“…The study showed that patients with skin lesions covering more than 1% body surface area or located above the waist were more likely to carry ACTB mutations. 22…”
Section: Geneticsmentioning
confidence: 99%